Efektivitas Eye Movement Desensitizion And Resprocessing (EMDR) Butterfly Hugs Sebagai Self Healing Stres Kerja Perawat: Literature Review - Endah, Rika; Khairani, Ilma; Sari Rezeki, Purnama (Universitas Haji Sumatera Utara, 2025)
Nurses are required to provide quality and excellent health services. Nurses are responsible for treating their patients until they recover psychologically. And have pressure and workload in a shift system. Such nursing conditions require nurses to carry out their responsibilities so that they can cause stress. The practice of psychotherapy called the EMDR butterfly hug should help nurses reduce stress. By using comforting thoughts, the butterfly hug is a therapy technique used to maintain emotional stability and calm the mind. The research method used is a narrative literature review of 11 references by taking from the Science Direct, Proquest, Ebsco and Google Scholar databases from 2019 to 2023 using the keywords